Utilization of Chitosan Elicitation on Biomass, Total Flavonoids, and Antioxidant Activity of Black Betel Callus (Piper betle L. var Nigra): Utilization of Chitosan Elicitation on Black Betel Callus (Piper betle L. var Nigra) - Nurindah Wanti, Yulia Tri; Wida Utami, Edy Setiti; Junairiah (Journal of Tropical Life Science, 2025)
Callus culture is a suitable method for the production of secondary metabolites. Elicitors can increase the content of secondary metabolites through the elicitation process. This study aims to determine the effect of chitosan elicitation on biomass, total flavonoids, and antioxidant activity of black betel callus. The research method is callus production by growing leaf explants on Murashige and Skoog (MS) medium with the addition of growth regulators Benzyl Amino Purin (BAP) 0.5 mg/L and 2,4-Dichlorophenoxy Acetic Acid (2,4-D) 2.0 mg/L. Furthermore, the callus was sub-cultured on MS medium with chitosan elicitor for four days. The data obtained was callus biomass. Extraction of callus to measure flavonoid content and antioxidant activity. The results showed that chitosan elicitation at 1.5 mg/L showed the most optimal biomass results, 1.22  ± 0.39 g fresh weight and 0.81 ± 0.17 g dry weight. Chitosan elicitation with 1.5 mg/L treatment showed the highest total flavonoid content of 9.52 ± 0.37 µg QE/g. The methanol extract of black betel callus resulting from chitosan elicitation has antioxidant activity. Callus treated with 2 mg/L chitosan showed the most substantial IC50 value of 53.60 ± 14.45 mg/L. Chitosan elicitation can effectively increase biomass, total flavonoids, and antioxidant activity of black betel leaf callus. Chitosan 1.5 mg/L is the optimum concentration for increasing biomass and total flavonoids, and chitosan 2 mg/L is the concentration that has the most effect on the antioxidant activity of black betel leaf callus.